2015
DOI: 10.5657/kfas.2015.0337
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Myxosporean Parasite Isolated from Emaciated Olive Flounders Paralichthys olivaceus on Jeju Island

Abstract: To investigate the causes of emaciation in cultured olive flounder Paralichthys olivaceus in Korea. We performed histological examinations and polymerase chain reaction (PCR) with a new primer set. In most cases, the most severe emaciation was observed in the abdominal area Using PCR on extracted livers, kidneys, spleens, gills, brains, and intestines, we found that areas around the kidneys and intestines were as almost always positive. In significantly emaciated fish, PCR was positive in all internal organs e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…Since the first detection of emaciation disease in cultured olive flounder of Korea, several studies have been performed to verify its aetiological agent, pathophysiological mechanism and clinical features (Choi et al., ; Kim, Jun, Park, Jeong, & Jeong, ; Kim et al., ; Sekiya et al., ). Interestingly, a Korean research group reported that a Parvicapsula anisocaudata caused emaciation in cultured olive flounder in Korea (Kim et al., ) whereas a Japanese research group identified E. leei as pathogen of the emaciation disease (Sekiya et al., ) even though these two studies investigated olive flounder produced in the same region (Jeju Island). Recently, we revealed that E. leei is a causative agent of emaciation disease in cultured olive flounder using molecular diagnostics (Shin, Sohn, Jin, Kang, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the first detection of emaciation disease in cultured olive flounder of Korea, several studies have been performed to verify its aetiological agent, pathophysiological mechanism and clinical features (Choi et al., ; Kim, Jun, Park, Jeong, & Jeong, ; Kim et al., ; Sekiya et al., ). Interestingly, a Korean research group reported that a Parvicapsula anisocaudata caused emaciation in cultured olive flounder in Korea (Kim et al., ) whereas a Japanese research group identified E. leei as pathogen of the emaciation disease (Sekiya et al., ) even though these two studies investigated olive flounder produced in the same region (Jeju Island). Recently, we revealed that E. leei is a causative agent of emaciation disease in cultured olive flounder using molecular diagnostics (Shin, Sohn, Jin, Kang, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…The production of fish comprises 50% of finfish culture. Since the first detection of emaciation disease in cultured olive flounder of Korea, several studies have been performed to verify its aetiological agent, pathophysiological mechanism and clinical features (Choi et al, 2012;Kim, Jun, Park, Jeong, & Jeong, 2015;Kim et al, 2011;Sekiya et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The death rate of olive flounders occurring within 1-3 weeks after the first symptoms appear is increasing. Fish infected with this illness show darkening of the body color, a decrease in weight, and bleeding (Kim et al 2015). The myxosporean emaciation disease has occurred in tiger puffer (Takifugu rubripes), parrotfish (Sparisoma cretense), and olive flounder (Ishimatsu et al 2007;Katharios et al 2014;Yasuda et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although external symptoms including abdominal emaciation and body darkening were observed, there is no clear information on exact life cycle has not been reported. In addition, PCR analysis of the olive flounders of Jeju island with the primer set of Enteromyxum leei (1589 bp), an etiologic agent of turbot myxosporean emaciation disease in Japan, a neighboring country of Korea, ruled out E. leei as the etiologic agent, as a negative reaction was observed (Kim et al 2015). We designed the specific primer set for detection of myxosporea from emaciated olive flounder in Korea (Kim et al 2015).…”
Section: Introductionmentioning
confidence: 99%